Medico-ethnobotanical survey of medicinal plants used in the treatment of skin diseases in Tiruppur District, Tamil Nadu, India - Prakasam Radha; Chinniaya Udhayavani; Raju Nagaraj; Kumarasamy Sivaranjani (Phytomedicine Plus)
Background and purpose: The present study aimed to identify, collect, and document the existing folklore knowledge on the utilization of medicinal plants to treat various common skin diseases such as Paronychia, Wounds, Carcinoma, Fissure foot, Scabies, Eczema, Melasma, Alopecia, Ringworm, Herpes, Psoriasis, Vitiligo etc. amongst the indigenous communities of Tiruppur District, Tamil Nadu. Study methods: Medico-ethnobotanical survey was carried out from November 2017 to November 2020 in five blocks of Tiruppur District, Tamil Nadu, India. The data were documented from 194 key informants by using semi-structured questionnaire. The documented data were analyzed using different quantitative indices including Use Value (UV), Relative frequency of Citation (RFC), and Frequency of Citation (FC). Results: Total of 86 species belonging to 42 families of angiosperm were recorded for their therapeutic uses against dermatological ailments. Out of which, herbs constitute the major portion with 31 species used for skin ailments. Cucurbitaceae is the most dominant family documented for skin diseases. Leaves found the most used part (52 species) in the preparation of herbal medicine in the form of decoction (Kashayam), juice (Charu), paste and powder (Chooranam). Twenty-seven types of skin diseases were recorded and treated using 86 species, among them paronychia is dominantly treated using 18 species followed by wounds, scabies, psoriasis. In the quantitative analysis, Tridax procumbens L. is observed with the highest UV 0.41 and 0.36 RFC value with 80 use reports reported by seventy informants followed by Citrus aurantifolia (Christm.) Sw., with UV of 0.32 and 0.30 RFC value, Acalypha indica L. recorded with 0.26 UV and 0.21 RFC value. Conclusion: Results of the present study revealed that still the urban/sub-urban inhabitants are using medicinal plants available in the vicinity of their residence and, also it has been observed that the knowledge on the usage of medicinal plants and the diversity of the same are alarming for existence. The documented medicinal plants provide a basis for developing cost-effective and culturally appropriate treatments for common skin diseases prevalent in the region. Integrating traditional knowledge with modern medical practices could enhance healthcare accessibility and sustainability.